1986
DOI: 10.1136/bmj.293.6554.1055
|View full text |Cite
|
Sign up to set email alerts
|

Muscle power after glucose-potassium loading in undernourished patients.

Abstract: The force-frequency characteristics and maximal relaxation rate of the adductor pollicis muscle were measured before and after 48 hours of intravenous loading with glucose (104-5 kJ (25 kcal)/ kg/24 h) and potassium (20 mmol(mEq)/500 ml glucose) in eight undernourished patients about to undergo surgery. Both variables of skeletal muscle performance, which were depressed when compared with data from 100 healthy volunteers, improved significantly after glucose-potassium loading. The improvement was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…However, we think it unlikely that changes in blood gases affected our results because no direct effect of acute hypoxia and hypercapnia/acidosis on MRR has been shown in humans [23]. Nevertheless, other metabolic influences of MRR on skeletal muscle, such as thyroid [24] and nutritional [25] status, were not controlled in our study.…”
Section: Discussionmentioning
confidence: 40%
“…However, we think it unlikely that changes in blood gases affected our results because no direct effect of acute hypoxia and hypercapnia/acidosis on MRR has been shown in humans [23]. Nevertheless, other metabolic influences of MRR on skeletal muscle, such as thyroid [24] and nutritional [25] status, were not controlled in our study.…”
Section: Discussionmentioning
confidence: 40%
“…We (19) and others (20) have also observed that fasted and hypocalorically fed rats and malnourished humans have a slower relaxation rate, perhaps, as shown herein, due to a fall in AGATP.…”
Section: Musclefree Mg2+mentioning
confidence: 82%
“…This suggests other physiologic factors are involved. The observations that muscle dysfunction begins within 24 h of fasting in humans [33] prior to a significant loss of nitrogen (and, therefore, muscle size), and that muscle function is normalized sooner than expected with refeeding [33][34][35][36][37] further supports the presence of other factors.…”
Section: Alteration In Muscle Size and Functionmentioning
confidence: 75%
“…Impairment of the swallow caused by a lack of available energy, therefore, should improve quickly with nutritional support. Chan et al [33] observed a return to normal muscle function parameters in malnourished surgical patients after 2 days of intravenous glucose and potassium administration. This quick response to energy substrate may explain the normal muscle function parameters observed by Shizgal et al [34] (see Table 2).…”
Section: Nutrition Supportmentioning
confidence: 97%
See 1 more Smart Citation